High-dose-rate brachytherapy boost for locally advanced cervical cancer: Oncological outcome and toxicity analysis of 4 fractionation schemes. (January 2022) - le Guyader, Maud; Lam Cham Kee, Daniel; Thamphya, Brice; Schiappa, Renaud; Gautier, Mathieu; Chand-Fouche, Marie-Eve; Hannoun-Levi, Jean-Michel
Highlights: Brachytherapy boost is a standard of care for locally advanced cervical cancer. High-dose-rate brachytherapy (HDR-BT) boost procedure is not standardized. The number of implants, fractions, doses and imaging differ in literature. Bi-fractionated HDR-BT in 1 implant is feasible with good oncological outcome. Bi-fractionated HDR-BT dose escalation slightly increases acute toxicity. Abstract: Purpose: Brachytherapy (BT) boost after radio-chemotherapy (RCT) is a standard of care in the management of locally advanced cervical cancer (LACC). As there is no consensus on high-dose-rate (HDR) BT fractionation schemes, our aim was to report the oncological outcome and toxicity profile of four different schemes using twice-a-day (BID) HDR-BT. Patients and methods: This was an observational, retrospective, single institution study for patients with LACC receiving a HDR-BT boost. The latter was performed with a single implant and single imaging done on day 1. The different fractionation schemes were: 7 Gy + 4x3.5 Gy (group 1); 7 Gy + 4x4.5 Gy (group 2); 3x7Gy (group 3) and 3x8Gy (group 4). Local (LFS), nodal (NFS) and metastatic (MFS) recurrence-free survival as well as progression-free survival (PFS) and overall survival (OS) were analyzed. Acute (≤6 months) and late toxicities (>6 months) were reported. Results: From 2007 to 2018, 191 patients were included. Median follow-up was 57 months [45–132] and median EQD210 D90 CTVHR was 84, 82 and 90 Gy for groups 2, 3 and 4 respectively (dosimetric data missing for group 1). The 5-year LFS, NFS, MFS, PFS and OS were 85% [81–90], 83% [79–86], 70% [67–73], 61% [57–64] and 75% [69–78] respectively, with no significant difference between the groups. EQD210 D90 CTVHR < 85 Gy was a prognostic factor for local recurrence in univariate analysis (p = 0.045). The rates of acute/late grade ≥ 2 urinary, digestive and gynecological toxicities were 9%/15%, 3%/15% and 9%/25% respectively. Conclusion: Bi-fractionated HDR-BT boost seems feasible with good oncological outcome and slightly more toxicity after dose escalation.